2020
DOI: 10.29303/jppipa.v6i2.411
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Science Teachers' Understanding of High Order Thinking Skills (HOTS) and Their Implementation in Learning

Abstract: This study aims to analyze and describe data on the understanding of YAPNUSDA elementary school teachers of High Order Thinking Skills (HOTS) and their implementation in learning. This study is a descriptive study that describes HOTS's understanding of the teacher and its implementation in learning. The data collection tool used was a questionnaire. The results of this study indicate that in general the data obtained is that the teachers in the study location schools do not yet understand about HOTS. They can'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
(7 reference statements)
1
6
0
Order By: Relevance
“…This can be seen from the low high-order thinking ability of physics teacher candidates which are still not as expected. This is in line with research Anggraeni et al (2020), the most frequently cited reason that also hinders teachers is that they do not understand HOTS and the technique of constructing instruments with verbs that measure HOTS.…”
Section: Introductionsupporting
confidence: 81%
“…This can be seen from the low high-order thinking ability of physics teacher candidates which are still not as expected. This is in line with research Anggraeni et al (2020), the most frequently cited reason that also hinders teachers is that they do not understand HOTS and the technique of constructing instruments with verbs that measure HOTS.…”
Section: Introductionsupporting
confidence: 81%
“…Other research conducted by Ramdiah, Abidinsyah, Royani, & Husamah (2019) revealed that the teacher's knowledge about HOTS is good but in its implementation is not in accordance with the understanding that has and is inconsistent in its implementation. The research conducted Anggraeni & Sole (2020) also revealed that for elementary school teachers in one of the eastern regions of Indonesia still do not understand and are not able to define HOTSbased learning. Based on previous research, it can be concluded that the learning process based on HOTS both in elementary school and senior high school still needs to be improved again.…”
Section: Introductionmentioning
confidence: 94%
“…Putri et al (2021) stated that in the 21st century, students must have higher order thinking skills (HOTS), the ability to argue, literacy skills, and so on. Anggraeni et al (2020) stated that in improving HOTS-based learning outcomes, teachers need first to understand HOTSbased learning to improve assessment tools such as student exam questions.…”
Section: Resultsmentioning
confidence: 99%